2023
DOI: 10.34659/eis.2023.84.1.520
|View full text |Cite
|
Sign up to set email alerts
|

The reporting of climate-related information by CSR leaders in Poland: a climate-related disclosures index

Abstract: The article measures the scope of reporting climate-related information by companies considered CSR leaders in Poland. An original tool is employed for that purpose: a climate-related disclosures index. First, a critical comparative analysis was performed of climate-related disclosure initiatives (regulations, guidelines, standards) to pinpoint the key and commonly required disclosures. Next, an original index of climate-related disclosures was designed. It helped compute index values for 20 companies perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Companies do not always demonstrate a high awareness of disclosing standardised environmental and climate aspects, which is confirmed by research measuring the scope of reporting climate-related information by companies recognised as CSR leaders in Poland using the climate-related disclosure index (Jastrzębska, 2023).…”
Section: Environmental Reporting -Legal Foundation and Literature Reviewmentioning
confidence: 92%
“…Companies do not always demonstrate a high awareness of disclosing standardised environmental and climate aspects, which is confirmed by research measuring the scope of reporting climate-related information by companies recognised as CSR leaders in Poland using the climate-related disclosure index (Jastrzębska, 2023).…”
Section: Environmental Reporting -Legal Foundation and Literature Reviewmentioning
confidence: 92%
“…• the impact of the Directive on the quantity and quality of information presented in ESG reports, including Carini et al (2018), Mio et al (2021), Ventera andvan Eck (2021), di Tullio et al (2019), Ottenstein et al (2022), Hummel and Szekely (2022), Aguado-Correa et al (2023), Jastrzębska (2023. The publications show that the Directive had a positive impact on the quantity, but not the quality, of non-financial information presented in thematic reports.…”
Section: An Overview Of the Literaturementioning
confidence: 99%
“…Various factors influence these differences. features at the company and market level are also of significant importance -both significant involvement in sustainable development issues and the industry's sensitivity to the environment, • the relationship between influencing factors and the quality of non-financial reporting, among others: Jastrzębska (2023). The publications critically assessed the effectiveness of the directive, highlighted the need to pay special attention to the actual contribution of companies to achieving the Sustainable Development Goals, and indicated the need to understand the differences in reporting on the Sustainable Development Goals in the EU.…”
Section: An Overview Of the Literaturementioning
confidence: 99%
“…Numerous researches indicate rising interest of companies for climate changes and actions, emphasizing that increasing number of companies join different global initiatives -The World Economic Forum's First Movers Coalition or Science Based Target Initiative -SBTi, United Nations' "Race to Zero" campaign, etc. (Jastrzebska, 2023;Principale & Pizzi, 2023;Chua et al, 2022;Hain et al, 2022). The trend of nonfinancial reporting, with the focus on climate-related information, has been accepted by the increasing number of companies worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The next part of the paper is conclusion, followed by the list of references. Jastrzebska (2023) researched the scope of reporting climate-related information of 20 companies considered as CSR leaders in Poland, by employing a climate-related disclosures index, covering 18 indicators, recommended by TCFD. The study showed that all climate-related disclosure initiatives of researched companies are in compliance with TCFD recommendations, but the value of index indicates that companies perceived as CSR leaders in Poland do not have high awareness of climate changes.…”
Section: Introductionmentioning
confidence: 99%